Environmental Exposures in the Etiology of Abortion: Placental Toxic and Trace Element Levels - Baser, Emre; kırmızı, Demet Aydogan; Turksoy, Vugar Ali; Onat, Taylan; Çaltekin, Melike Demir; Kara, Mustafa; Yalvac, Ethem Serdar (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Purpose Intensive research has been conducted on the effects of toxic and trace elements on pregnancy. Previous studies indicated a possible relationship between placental levels of these elements and first-trimester abortion; however, their effects on the further gestational weeks are not clear. This study aimed to investigate the effect of changes in the levels of placental trace and toxic elements on second-trimester abortion.Methods The patient group consisted of 30 women with missed abortion. The control group comprised 60 healthy term and singleton pregnant women who gave birth. Placental samples were obtained from the patients and the healthy controls, and the concentrations of placental elements were measured using inductively coupled plasma mass spectrometry.Results In the abortion group, placental arsenic, cadmium, mercury, lead, antimony, tin, cobalt, manganese, and selenium levels were significantly higher than those of the control group (p<0.05). Antimony was determined as an independent predictor with an odds ratio of 6.1 in toxic elements (p=0.025), and selenium was determined as an independent predictor with an odds ratio of 2.3 in trace elements (p=0.015).Conclusion The changes in trace element and toxic element levels, especially an increase in antimony and selenium, in placental tissue due to environmental exposure may play an important role in second-trimester abortion.
Keywords: second-trimester abortions; heavy metal; trace element; toxic element; environmental exposure